Narrative Medicine Workshops for Obstetrics and Gynecology Residents and Association With Burnout Measures. (October 2016) - Winkel, Abigail Ford; Feldman, Nathalie; Moss, Haley; Jakalow, Holli; Simon, Julia; Blank, Stephanie
Abstract : OBJECTIVE: To determine whether a workshop Narrative Medicine curriculum can improve burnout among obstetrics and gynecology residents. METHODS: A Narrative Medicine curriculum was conducted at three obstetrics and gynecology training programs. An explanatory research design examined correlation between Narrative Medicine attendance and changes in survey responses. Residents completed a pretest and 1-year posttest survey that included validated measures of burnout and empathy. A within-participants design used baseline pretest scores as an internal control and measured changes in individual scores. The primary outcome of the study was change in burnout rates. Mann–Whitney U and Kruskal–Wallis tests were used to analyze the data. RESULTS: A total of 66 residents at three institutions participated in the Narrative Medicine curriculum. Of those, 54 (81%) enrolled in the study by completing any part of the surveys, and 43 (80%) of those enrolled had complete data for analysis. Burnout was high on all Maslach Burnout Inventory subscales and increased over 1 year. Participants with high Narrative Medicine attendance had decreased burnout on the Emotional Exhaustion subscale (−4.1 [±8.1]) points compared with an increase of 0.5 (±6.0) for low-attendance participants ( U =134, P =.02, d=0.65). Lower self-care ratings were associated with improved Personal Accomplishment (+0.5 [±5.0]) compared with +2.0 (±2.7), U =84, P =.01]. Other characteristics did not significantly correlate with burnout or empathy. CONCLUSION: Burnout was high and worsened over time among obstetrics and gynecology residents in these three programs. Higher attendance at Narrative Medicine workshops was associated with improved Emotional Exhaustion. Abstract : A multicenter study of a reflective writing curriculum reveals that residents with higher attendance have reduced burnout compared with those with lower attendance after 1 year.